Dual Diagnosis in the Context of Judicial Intervention: Challenges for Building Integrated Social Work Responses: https://doi.org/10.60543/ts_iss.vi10.11727 ("Temas Sociais" Journal, 2026)
Dual Diagnosis, defined as the coexistence of a mental disorder and a substance use disorder, represents a major challenge for health, justice, and social protection systems, requiring integrated responses. This study aimed to analyse how Dual Diagnosis is addressed in the intervention developed by the Portuguese Directorate-General for Reintegration and Prison Services (Direção-Geral de Reinserção e Serviços Prisionais – DGRSP) and to discuss its implications for Social Work practice. A qualitative, exploratory and descriptive approach was adopted, based on the documentary analysis of six case files involving individuals with Dual Diagnosis. Content analysis identified four key dimensions: social vulnerabilities, clinical heterogeneity, fragmented recognition of Dual Diagnosis, and limitations in interinstitutional coordination. The findings show that the simultaneous identification of mental illness and substance use does not necessarily translate into the recognition of Dual Diagnosis as an integrated condition, influencing assessment and intervention strategies. The study highlights the need for coordinated responses involving mental health, addiction services, the justice system, and social protection, while emphasising the role of Social Work in promoting integrated, person-centred interventions.
Keywords: Dual Diagnosis; Social Work; Justice system; Integrated intervention; Social reintegration